2002
DOI: 10.1093/gerona/57.6.m347
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Habits and Compression of Morbidity

Abstract: These results make a compelling argument for the reduction and postponement of disability with healthier lifestyles as proposed by the compression of morbidity hypothesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
98
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(107 citation statements)
references
References 17 publications
6
98
0
3
Order By: Relevance
“…Longitudinal observational studies suggest that regular physical activity cannot only extend life expectancy, but also to reduce the incidence of disability associated with aging [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal observational studies suggest that regular physical activity cannot only extend life expectancy, but also to reduce the incidence of disability associated with aging [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Linking "breaking into a sweat" and the risk of osteoarthritis 16 may seem funny and tongue-in-cheek 17 , but there is little humor in this implication. Exercise is arguably the most important treatment for OA 1,2,18,19 . It strengthens the joint structures, retards disability, stabilizes the joint, improves metabolism in the articular cartilage, increases endurance, improves quality of life, and wards off comorbidities.…”
Section: Rheumatologymentioning
confidence: 99%
“…It has few problems over a very wide range of lifetime activity 1,2,3 . Its value is recognized by medical and federal authorities, American College of Rheumatology guidelines, self-management programs, international health organizations, and the media 18,19 . Rheumatologists must aggressively advise colleagues and encourage patients to examine their physical function activities and to improve exercise activities whenever possible.…”
Section: Rheumatologymentioning
confidence: 99%
“…Recent studies suggested that improvement in health behaviors, such as better nutrition, smoking reduction, or increase in physical activities, would reduce morbidity more than increase longevity (82)(83)(84)(85)(86). Thus, if future increases in life expectancy are due to better behaviors, they could also be accompanied by larger increases in disability-free life expectancy leading to a compression of disability.…”
Section: Disability Versus Longevitymentioning
confidence: 99%
“…Many arguments go in this direction: a better adult life, a better educational level (54), and better health practices (55,56,94). All could lead to a compression of morbidity phase, which Austria, France, and the United States know today (1,85). However, progress continues, particularly in the improved environment and services provided to the oldest-old.…”
Section: A Draft Proposalmentioning
confidence: 99%